ROLE OF IMMUNOHISTOCHEMICAL ANALYSISIN EVALUATION OF PREGRAVID ENDOMETRIUM IN PATIENTS UNDERGOING IN-VITRO FERTILIZATION PROGRAM - V. A. Krutova; Ya. A. Kovalenko; L. M. Chuprinenko; A. A. Ordokova; O. V. Tarabanova (Сеченовский вестник)
Uterine disorders can considerably contribute to infertility. In order to overcome many different causes of female infertility a complex of diagnostic and therapeutic procedures was established. More than 100 bioactive substances inﬂuence the process of nidation. Uteroplacental relations are key factor of onset and normal course of pregnancy. The aim of current research is to evaluate prognostic value of expression of steroid hormone receptors and Ki-67 protein in pregravid endometrium of patients with positive results of in-vitro fertilization program. Research included 167 patients who underwent IVF and embryo transfer program in Base Clinic of Obstetrics and Gynecology, Krasnodar, in 2016-2017 years. Two groups were formed as follows: the 1st group was made of 72 patients who had pregnancy after IVF program and had full term delivery; the 2nd group was composed of 95 women with the negative result after IVF program. All patients had been examined according to the Ministry of Healthcare Order№ 107n “On applying assisted reproductive technologies, contraindications and limitations of their use” and had their ﬁrst IVF program. The endometrial biopsy was performed on day 8-11 of menstrual period in order to conduct histological and immunohistochimical analyses. IHC showed irregular expression of steroid hormone receptors in endometrial glands and stroma and altered proliferative activity of those structures in women with unsuccessful IVF. Assessment of steroid hormone receptors expression and protein Ki-67 expression may be considered as additional prognostic criteria of success in IVF. Immunohistochemical analysis of pregravid endometrium can improve diagnosis of uterine causes of infertility.